2022
DOI: 10.3390/medsci10010005
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis: Coronary Artery Calcium Score and COVID-19 Prognosis

Abstract: Background: Multiple studies have investigated the correlations of mortality, mechanical ventilation, and intensive care unit (ICU) admissions with CAC scores. This analysis overviews the prognostic capability of CAC scoring in mortality, mechanical ventilation, and ICU admission for hospitalized COVID-19 patients. Methods: Online search was conducted on PubMed, Cochrane Library, and Scopus from inception to 22 November 2021 to identify studies involving CAC scores in relation to ICU admission, mechanical vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…By a literature search, we found all our selected factors were addressed in other studies and were shown to be significantly associated with the COVID-19 disease severity. Here is a partial summary: Low calcium level is associated with poor prognosis of COVID-19 ( Filippo et al, 2020 , Liu et al, 2020 , Lee et al, 2022 , probably due to its role in viral infection and replication. Higher neutrophil/lymphocyte ratio (NLR) is known to be associated with severity of COVID-19 ( Zhang et al, 2020 , Ma et al, 2020 , Ulgen et al, 2021 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…By a literature search, we found all our selected factors were addressed in other studies and were shown to be significantly associated with the COVID-19 disease severity. Here is a partial summary: Low calcium level is associated with poor prognosis of COVID-19 ( Filippo et al, 2020 , Liu et al, 2020 , Lee et al, 2022 , probably due to its role in viral infection and replication. Higher neutrophil/lymphocyte ratio (NLR) is known to be associated with severity of COVID-19 ( Zhang et al, 2020 , Ma et al, 2020 , Ulgen et al, 2021 .…”
Section: Discussionmentioning
confidence: 92%
“…Low calcium level is associated with poor prognosis of COVID-19 ( Filippo et al, 2020 , Liu et al, 2020 , Lee et al, 2022 , probably due to its role in viral infection and replication.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews mentioned signs of cardiac injury caused by exacerbations of preexisting conditions resulting in myocardial ischemia [ 64 , 66 ]. The role of hypoperfusion-related cardiac injury was supported by a review of coronary artery calcium score impact on mortality rates in COVID-19 patients, finding a two-fold increase in patients with a higher score [ 69 ]. Pediatric reviews showed a high incidence of clinically suspected myocarditis in children presenting with multisystem inflammatory syndrome [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Objective findings highlight the hypothesis of a virus-triggered hyperinflammatory response [ 63 , 64 , 65 , 66 , 67 , 68 ]. This assumption is complemented by a high incidence of clinically suspected myocarditis in pediatric multisystem inflammatory syndrome [ 50 , 70 , 71 , 72 , 73 ] and autopsy findings of cardiac injury being a consequence of imbalanced immune response, hypercoagulation and hyperperfusion, pre-existing conditions or multiorgan failure [ 61 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. In addition, COVID-19 vaccine safety reviews had low rates of CMR and EMB confirmation [ 17 , 84 , 85 , 86 , 87 ], causing difficulties to determine whether these reactions meet myocarditis criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Low calcium level is associated with poor prognosis of COVID-19 (Di Filippo et al, 2020; Liu et al, 2020; Lee et al, 2022), probably due to its role in viral infection and replication.…”
Section: Discussionmentioning
confidence: 99%